(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2023)
This study includes a semiotic analysis of the KAKR Bamboo Hall facade. This is inspired by the architecture and surroundings of the building, which a young vernacular architect created. The first steps in conducting research on buildings are identification studies of the local environment, local culture, and the data utilized in the design process. This study makes use of semiotic theory by Charles Jenks and employs a quantitative research methodology with a descriptive approach. To obtain actual field data, the research began with a direct survey of the research location. A test on semiotics-related architectural theory was conducted using this data. The objective of this study is to provide a foundation or point of reference for the accuracy of the design work that will subsequently be performed on the nearby buildings. This, it is said, is because the village will eventually transform into a historical tourism destination. The findings show that Semiotic trichotomy indicators and Peirce’s semiotic theory are compatible. The research’s output is a design concept that uses a vernacular building approach in the Buluh Awar area. It does this by emphasizing semiotic trichotomy—the relationship between semiotic concepts and physical structures—in the form of buildings.